Academic Writing Training Programs to Developing Teachers’ Writing Skills for Publication - Venny Karolina; Yohanes Bahari; Rustiyarso Rustiyarso; Amrazi Zakso; Yusawinur Barella (Universitas Muhammadiyah Enrekang, 2023)
This action research-based writing training is a component of the community service initiative organized by social studies lecturers at the Teacher Training Faculty of Tanjungpura University. The training adopted an action research approach, which involved some cycles, each comprising planning, implementation, observation, and reflection stages. This approach was chosen to encourage participants to share their insights to improve the training quality. The research goal was to gather teachers' perceptions and recommendations for enhancing the quality of action research-based academic writing training. The study involved 33 secondary school Social Studies teachers taking place at SMK 2 Singkawang. To collect data, an open-ended questionnaire was utilized. The results revealed that teachers faced challenges in accessing internet resources and suggested extending the duration of the training. They also recommended providing more comprehensive information and examples for each section of the research article. Lastly, the teachers expressed a positive view of the training.